Urinary 1H-NMR Metabolomics Can Distinguish Pancreatitis Patients from Healthy Controls - Lusczek, Elizabeth Rose; Paulo, Joao A; Saltzman, John R; Kadiyala, Vivek; Banks, Peter A; Beilman, Greg; Conwell, Darwin L (JOP. Journal of the Pancreas, 2013)
Context The characterization of the urinary metabolome may yield biomarkers indicative of pancreatitis. Objectives We establish a non-invasive technique to compare urinary metabolic profiles in patients with acute and chronic pancreatitis to healthy controls. Methods Urine was obtained from healthy controls (HC, n=5), inpatients with mild acute pancreatitis (AP, n=5), and outpatients with chronic pancreatitis (CP, n=5). Proton nuclear magnetic resonance spectra were obtained for each sample. Metabolites were identified and quantified in each spectrum; resulting concentrations were normalized to account for differences in dilution among samples. Kruskal-Wallis test, post-hoc Mann-Whitney U tests, and principal component analysis were performed to identify metabolites that discriminate healthy controls, acute pancreatitis, and chronic pancreatitis. Results Sixty metabolites were identified and quantified; five were found to differ significantly (P<0.05) among the three groups. Of these, citrate and adenosine remained significant after validation by random permutation. Principal component analysis demonstrated that healthy control urine samples can be differentiated from patients with chronic pancreatitis or acute pancreatitis; chronic pancreatitis patients could not be distinguished from acute pancreatitis patients. Conclusions This metabolomic investigation demonstrates that this non-invasive technique offers insight into the metabolic states of pancreatitis. Although the identified metabolites cannot conclusively be defined as biomarkers of disease, future studies will validate our findings in larger patient cohorts. Image: Boxplots of two significant metabolites.